Sejarah Perkembangan Marga Pangkalan Balai Tahun 1950-1984 - Vebiana Anugrah Rezni; Dedi Irwanto (Pattingalloang : Jurnal Pemikiran Pendidikan dan Penelitian Kesejarahan, 2025)
This study aims to examine the development of the Pangkalan Balai clan during the Old Order and New Order, and to analyze the impact of the elimination of the clan system on the local community. The method used is historiography with a multidisciplinary approach from social sciences, including politics, economics, sociology, and anthropology. The research findings show that during the Old Order, the Pangkalan Balai clan was led by Pasirah who had legal legitimacy and implemented an organized customary government system. The clan's economy developed independently through various sources of income, while socio-cultural traditions, such as Ande-Ande Panjang and Timbang Kepala Kebo, reflected the values of togetherness of the Malay community. During the New Order, although the clan was still recognized, there were adjustments in the implementation of clan rights and changes in the procedures for electing Pasirah and its apparatus. The community's economy continued with government support in the fields of agriculture and plantations, which helped increase crop yields. On the socio-cultural side, despite the pressure to adapt to modernization, the community remained committed to preserving their traditions and cultural values. However, the abolition of the clan system in 1983 resulted in the loss of customary rights and the transfer of land management to the village government, as well as eliminating the role of Pasirah and clan apparatus in government. Although the formal structure was abolished, socio-cultural values and traditions are still maintained to this day.